2016
DOI: 10.4103/1119-3077.179291
|View full text |Cite
|
Sign up to set email alerts
|

Acute and intermittent testicular torsion: Analysis of presentation, management, and outcome in South East, Nigeria

Abstract: Late presentation was observed, especially in the intermittent variety. Delay occurred both at pre- and intra-hospital phases. Testicular salvage rate may be improved by physician/health worker and community enlightenment. Adoption of local anesthetic may reduce intrahospital delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
4
0
6
Order By: Relevance
“…Left untreated, the almost universal outcome is testicular hemorrhagic infarction. The disease is a frequent cause of organ loss by either orchidectomy or atrophy, especially in emerging countries ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Left untreated, the almost universal outcome is testicular hemorrhagic infarction. The disease is a frequent cause of organ loss by either orchidectomy or atrophy, especially in emerging countries ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…This miserable outcome is still commonly seen in our environment. [14] The overall salvage rate is very low in late presentation, delayed referral, and surgical intervention. [1,2] Peeraully et al [15] in a single-center retrospective analysis of the source of referral to a tertiary hospital for emergency scrotal exploration found that the orchidectomy rate was higher with those referred either from primary care centers (43%) or transferred from other hospitals (50%) when compared to patients who presented directly to their emergency department (23%).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, existen reportes de manejo conservador mediante rectificación manual mediante maniobras externas de la torsión que puede ser otra opción, sin resolver la patología de base y con el riesgo de recurrencias y progresión a necrosis que resulte en orquiectomía del testículo con episodios previos de torsiones intermitentes, por lo que se recomienda la orquidopexia programada bilateral. (13,14) Los signos encontrados durante el ultrasonido Doppler incluyen ausencia del flujo, que en los casos de torsión intermitente se asocia en un 79% al signo en remolino en la escala de grises, las imágenes con Doppler color o pseudomasa en el cordón, (15) 10% presentan un engrosamiento "boggy" o pantanoso del cordón y 10% tienen una apariencia normal. (3) Es importante una alta sospecha diagnóstica y un diagnóstico oportuno para esta patología, dado que el tratamiento tardío comprende la orquiectomía del testículo necrótico y la orquidopexia del testículo contralateral.…”
Section: Discussionunclassified